A non-linear procedure for the numerical analysis of crack development in beams failing in shear - P. Bernardi; R. Cerioni; E. Michelini; A. Sirico (Fracture and Structural Integrity)
In this work, a consistent formulation for the representation of concrete behavior before and after cracking has been implemented into a non-linear model for the analysis of reinforced concrete structures, named 2D-PARC. Several researches have indeed pointed out that the adoption of an effective modeling for concrete, combined with an accurate failure criterion, is crucial for the correct prediction of the structural behavior, not only in terms of failure load, but also with reference to a realistic representation of crack initiation and development. This last aspect is particularly relevant at serviceability conditions in order to verify the fulfillment of structural requirements provided by Design Codes, which limit the maximum crack width due to appearance and durability issues. In more details, a constitutive model originally proposed by Ottosen and based on non-linear elasticity has been here incorporated into 2D-PARC in order to improve the numerical efficiency of the adopted algorithm, providing at the same time an accurate prediction of the structural response. The effectiveness of this procedure has been verified against significant experimental results available in the technical literature and relative to reinforced concrete beams without stirrups failing in shear, which represent a problem of great theoretical and practical importance in the field of structural engineering. Numerical results have been compared to experimental evidences not only in terms of global structural response (i.e. applied load vs. midspan deflection), but also in terms of crack pattern evolution and maximum crack widths.